PERSEPSI PENGGUNAAN SWISHMAX UNTUK PENGEMBANGAN MEDIA PEMBELAJARAN OLEH GURU SEKOLAH DASAR DI GUGUS 3 KAMANG MAGEK KABUPATEN AGAM - Yeka Hendriyani; Vera Irma Delianti; Lativa Mursyida (Universitas Negeri Padang, 2017)
The purpose of this article is to find out the perceptions of primary school teachers on the use of Swishmax applications for the development of instructional media. Teachers' perceptions of the use of Swishmax applications for the development of instructional media are closely related to student learning achievement. Learning media generated with Swishmax applications that match the students' wishes will keep them motivated in learning. This article analyzes the data done descriptively. The data obtained in this article comes from questionnaire data and unstructured interview data. The result of this article is the perception of Swishmax's use for the development of instructional media by elementary school teachers in positive category. Keywords: Perception Teachers, Instructional Media, Swishmax